The Effect of Financial Targets and Financial Stability on Financial Statement Fraud in the Mining Sector Registered in LQ-45 for the 2019–2023 Period - Nurjanah, Cici; Foster, Bob; Musadat, Irfan Achmad (CV ODIS, 2025)
This study aims to determine the picture and influence of Financial Targets and Financial Stability on financial statement fraud. This study uses a quantitative method with a descriptive and verifiable approach, the secondary data in this study is accessed through www.idx.co.id. The population of this study is companies in the mining sector listed in LQ-45 for the 2019-2023 period with a population of 50 financial statements from 10 companies during the 2019-2023 period. In the sampling process, the technique used is purposive sampling by producing 20 financial reports from 4 companies during the 2019-2023 period. Based on the results of the hypothesis test, it was obtained that the results of the t-test partially concluded that the Financial Target had no effect on Financial Statement Fraud with an effect of 0.1%. Meanwhile, the Financial Stability variabel partially did not affect Financial Statement Fraud with an influence of 3.0%. And simultaneously, Financial Targets and Financial Stability have no effect on financial statement fraud, the amount of influence is -0.70% on the Mining Sector Registered in LQ-45 for the 2019-2023 Period.